THE RELATIONSHIP BETWEEN LONGITUDINAL FRACTIONAL SHORTENING AND DIASTOLIC FUNCTION IN INDIVIDUALS WITH HYPERTENSION AND THE GLOBAL LONGITUDINAL STRAIN VALUE IN PATIENTS WITH HYPERTENSIVE HYPERTROPHY FOR SUBCLINICAL LV DYSFUNCTION. - Keerthana M.P., Abinayasri G, Sandhiya R, Sherine Karunya W, Abishkauf Jenish Beautlin, Sambathkumar L, Surathul Samrin, Kishore Kanna (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Background: Patients with hypertrophy can measure the global longitudinal strain value for subclinical left ventricular failure, which may assist lower cardiovascular morbidity and death, if longitudinal fractional shortening and diastolic function are detected early. The study aims to forecast the incidence, prevalence, and early identification of GLS in hypertension hypertrophy patients and longitudinal shortening and LV dysfunction in hypertensive patients. Material: Our prospective Observational study included 81 cases hypertension patients and 81 healthy controls, all had done conventional echocardiography 2D m-mode and Global longitudinal strain. Results: Our research demonstrates that hypertension patients with left ventricular hypertrophy have significantly lower global longitudinal strain values and strain ejection fractions. In our study population of 162 patients, 53 patients are found to have normal LFS value>1.33 and remaining 109 patients had abnormal LFS values <1.33. Among 81 patients with hypertension 19 patients had normal LFS values with diastolic dysfunction Remaining 62 patients had abnormal LFS values whereas 57 patients with diastolic dysfunction and 5 with normal diastolic function. When identifying subclinical impairment, speckle tracking echocardiogram is more important than 2D conventional echocardiography. Conclusion: Global longitudinal strain echocardiography identified early deterioration of LV systolic function in hypertensive patients with maintained EF in traditional 2D m-mode and hypertrophied LV as a result of pressure overload.